"Baby Wants Tacos": Analysis of Health-Related Facebook Posts from Young Pregnant Women. - Marshall, Elizabeth; Moon, Margaret Abigail; Mirchandani, Anicia; Smith, D. Grace; Nichols, Lauren P.; Zhao, Xinyan; Vydiswaran, V. G. Vinod; Chang, Tammy (Maternal & Child Health Journal, 2019)
Objectives Pregnant young women gain more weight than recommended by the National Academy of Medicine, increasing the likelihood of adverse maternal and fetal outcomes. The purpose of this study is to use online social media to understand beliefs and practices surrounding weight gain, diet and exercise during pregnancy among young women. Methods Facebook posts were mined from young women ages 16 to 24 during pregnancy who were consented from two Midwest primary care clinics serving low-income communities. Natural language processing was used to identify posts related to weight gain, exercise and diet by keyword searching. Two investigators iteratively coded the mined posts and identified major themes around health behaviors. Outcome measures included the frequency of posts and major themes regarding health behaviors during pregnancy. Results Participants (n = 43) had a mean age of 21 (SD 2.3), and the largest subgroups identified as black (49%; 26% white, 16% Hispanic, 9% other) and having graduated from high school (49%; 24% completed some high school and 24% completed at least some post-secondary education). Among the 2899 pregnancy posts analyzed, 311 were related to weight. Major themes included eating behaviors and cravings (58% of identified posts), body image (24%), the influence of family, partners and friends (14%), and the desire to exercise (4%). Conclusions for practice Facebook posts revealed that young women often frame their thoughts and feelings regarding weight gain in pregnancy in the context of food cravings and body image and that friends and family are important influencers to these behaviors.